(untitled) (Journal of Economic Research & Business Administration, 2015)
The development and establishment of a market economy in our country have long been put in charge of virtually any business needs and requirements of buyers. All companies do not realize the time priority of this production , could not hold in today’s competitive environment. Thus, the ever increasing role of industrial marketing as activities aimed at identifying and satisfying customer needs, activities designed primarily to increase the efficiency of the organization , ensuring its profitability. Analysis of the existing theoretical foundations of marketing has shown that the main object of the study is the consumer markets, while industrial markets neglected. At the organization of research conducted in the industrial markets are used as a rule principles and techniques developed for the consumer market. The peculiarities of the organization and operation of the industrial markets are taken into account enough. In this regard, the present article describes the features of industrial marketing, analyzed the behavior of industrial buyers formulate marketing strategies of the industrial markets of the consumer, provides specific formula to determine the competitiveness of the industry. Also, in this paper we consider the experience of foreign countries in the study and use of the principles and methods of industrial marketing, offers advice to develop marketing strategies for the company.